Migrant Electoral Rights (MER): New Data from 165 Countries and Six Decades [R Scripts] - Sebastián Umpierrez de Reguero (18960909) (2025)
The supplementary R scripts accompany the manuscript Migrant Electoral Rights (MER). New Data from 165 Countries and Six Decades. They provide the full replication code used to build, validate, and analyze the MER dataset.